BREEDING ASSESSMENT OF HETEROPLOID CROSSES IN THE DEVELOPMENT OF TRIPLOID APPLE VARIETIES - E. N. Sedov; G. A. Sedysheva; Z. M. Serova; N. G. Gorbacheva; S. A. Melnik (Вавиловский журнал генетики и селекции)
A 40-year work on apple breeding on a polyploidy level has shown that the most promising crosses for reliable regular development of triploid varieties are 2x × 4x and 4x × 2x.Cytological control shows that reciprocal combinations are unequal in the output of seedlings with different ploidy. In crosses 2x × 4x the output of triploid seedlings is higher than in crosses 4x × 2x. The cause is the different degrees of autogamy in parental tetraploid forms: when nonemasculated flowers are pollinated, highly autogamous forms are preferably pollinated with their own pollen. When larger number of triploid plants is required in crosses 4x × 2x flowers of these forms should be emasculated.The production and biological characteristics of eight apple varieties with stable fruit-bearing and highly marketable fruit, are given in this paper.